(untitled) (Research, Society and Development, 2022)
The objective was to review, among individuals of different skin colors and ethnic groups, how the effectiveness and safety of drugs could be influenced by pharmacokinetics variations resulting from genetic polymorphisms in the cytochrome P-450 enzyme system (CYP-450). This is a systematic review study, with a descriptive and observational approach. The systematic review protocol was registered on the international platform Prospective Register of Systematic Reviews under the identification number 25581111. Data collection was performed on Medical Literature Analysis and Retrieval System Online (MedLine) through PubMed, Latin American Literature, and the Caribbean Health Sciences (LILACS), as well as the Scientific Electronic Library Online (SciELO). Six CY450 genetic polymorphisms that may affect pharmacodynamic and pharmacokinetics parameters of therapy in drug users of different ethnic and skin color was identified and described to drugs as Olanzapine, Efavirenz, and Irinotecan. However, the results found did not demonstrate the existence of clinically significant differences when evaluating the aspects of safety and effectiveness of the drugs, despite the identification of polymorphisms in the CYP450 enzyme system that influenced these parameters. The findings point to the identification of individual genotypes, without ethnic or skin color cut, to provide a better application of precision medicine, thus helping to make therapeutic decisions in clinical practice in the light Evidence-Based medicine.